An experimental-numerical study of the adhesive static and dynamic friction of micro-patterned soft polymer surfaces. (5th November 2019) - Berardo, Alice; Costagliola, Gianluca; Ghio, Simone; Boscardin, Maurizio; Bosia, Federico; Pugno, Nicola M.
Abstract: New possibilities have emerged in recent years, with the development of high-precision fabrication techniques, to exploit microscale surface patterning to modify tribological properties of polymeric materials. However, the effect of surface topography, together with material mechanical parameters, needs to be fully understood to allow the design of surfaces with the desired characteristics. In this paper, we experimentally assess the effect of various types of micropatterned Polydimethylsiloxane surfaces, including anisotropic ones, on macroscopic substrate friction properties. We find that it is possible, through surface patterning, to modify both static and dynamic friction coefficients of the surfaces, demonstrating the possibility of achieving tunability. Additionally, we compare experimental observations with the numerical predictions of a 2D Spring-Block model, deriving the material parameters from tests on the corresponding flat surfaces. We find a good quantitative agreement between calculated and measured trends for various micropattern geometries, demonstrating that the proposed numerical approach can reliably describe patterned surfaces when appropriate material parameters are used. The presented results can further contribute to the description and understanding of the frictional effects of surface patterning, with the aim of achieving surfaces with extreme tunability of tribological properties. Graphical abstract: Unlabelled Image Highlights: The effect of patterning on static/dynamic friction of soft polymer surfaces is investigated experimentally and numerically Micro-patterns modify macroscopic static friction coefficients between -57 and +20% and dynamic ones between -35 and 30% Calculations using an in-house developed 2D Spring-Block model are in good agreement with experimental results